Combination of Chinese Herbal Medicines and Conventional Treatment versus Conventional Treatment Alone in Patients with Acute Coronary Syndrome after Percutaneous Coronary Intervention (5C Trial): An Open-Label Randomized Controlled, Multicenter Study. (2nd July 2013) - Wang, Shao-Li; Wang, Cheng-Long; Wang, Pei-Li; Xu, Hao; Liu, Hong-Ying; Du, Jian-Peng; Zhang, Da-Wu; Gao, Zhu-Ye; Zhang, Lei; Fu, Chang-Geng; Lü, Shu-Zheng; You, Shi-Jie; et al.
Abstract : Aims. To evaluate the efficacy of Chinese herbal medicines (CHMs) plus conventional treatment in patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). Methods and Results. Participants (n = 808 ) with ACS who underwent PCI from thirteen hospitals of mainland China were randomized into two groups: CHMs plus conventional treatment group (treatment group) or conventional treatment alone group (control group). All participants received conventional treatment, and participants in treatment group additionally received CHMs for six months. The primary endpoint was the composite of cardiac death, nonfatal recurrent MI, and ischemia-driven revascularization. Secondary endpoint was the composite of readmission for ACS, stroke, or congestive heart failure. The safety endpoint involved occurrence of major bleeding events. The incidence of primary endpoint was 2.7% in treatment group versus 6.2% in control group (HR, 0.43; 95% CI, 0.21 to 0.87; P = 0.015 ). The incidence of secondary endpoint was 3.5% in treatment group versus 8.7% in control group (HR, 0.39; 95% CI, 0.21 to 0.72; P = 0.002 ). No major bleeding events were observed in any participant. Conclusion. Treatment with CHMs plus conventional treatment further reduced the occurrence of cardiovascular events in patients with ACS after PCI without increasing risk of major bleeding.